HIV infection predominantly affecting children in Sindh, Pakistan, 2019: a cross-sectional study of an outbreak. Issue 3 (March 2020) - Mir, Fatima; Mahmood, Faisal; Siddiqui, Amna Rehana; Baqi, Shehla; Abidi, Syed Hani; Kazi, Abdul Momin; Nathwani, Apsara Ali; Ladhani, Amerta; Qamar, Farah Naz; Soofi, Sajid Bashir; Memon, Sikander Ali; Soomro, Jamila; et al.
Summary: Background: In April 2019, an HIV screening camp for all ages was established in response to a report of an unusually large number of paediatric HIV diagnoses in Larkana, Pakistan. We aimed to understand the clinical profile of the children who registered for HIV care. Methods: In this cross-sectional study, we review the outbreak response from the government, academia, and UN agencies in Larkana, Sindh, Pakistan. We report age-stratified and sex-stratified HIV prevalence estimated among individuals screened. For children who registered for HIV care, clinical history of previous injections and blood transfusions, HIV disease stage, hepatitis B and hepatitis C status, and CD4 count was abstracted from clinical records from Sindh AIDS Control Program HIV Clinic (Shaikh Zayed Childrens Hospital, Larkana, Pakistan) and analysed using percentages, χ 2 tests, and weight-for-age Z scores. We also analysed data for parents who were tested for HIV. Findings: Between April 24, and July 15, 2019, 31 239 individuals underwent HIV testing, of whom 930 (3%) tested positive for HIV. Of these, 763 (82%) were younger than 16 years and 604 (79%) of these were aged 5 years and below. Estimated HIV prevalence was 3% overall; 7% (283 of 3803) in children aged 0–2 years, 6% (321 of 5412) in children aged 3–5 years, and 1% (148 of 11 251) in adults aged 16–49 years. Of the 591 children who registered for HIV care, 478 (81%) were 5 years or younger, 379 (64%) were boys, and 315 (53%) of 590 had a weight-for-age Z score of −3·2. Prevalence of hepatitis B surface antigen was 8% (48 of 574) and hepatitis C antibody positivity was 3% (15 of 574). Of children whose mothers tested for HIV, only 39 (11%) of 371 had HIV-positive mothers. Most children (404 [89%] of 453) reported multiple previous injections and 40 (9%) of 453 reported blood transfusions. Interpretation: This HIV outbreak is unprecedented among children in Pakistan: a 54% increase in paediatric HIV diagnoses over the past 13 years. The outbreak was heavily skewed towards young children younger than 5 years, with a predominance of boys. Epidemiological and molecular studies are needed to understand the full extent of the outbreak and its drivers to guide HIV control strategies. Funding: None.